REVITALISASI PENCAK SILAT MELALUI FESTIVAL SEREPAN PATALEKAN USIK SANYIRU DENGAN OPTIMALISASI TEKNOLOGI DIGITAL BERBASIS CULTURAL VISUALIZATION - Reza, Faisal; Sarifiyono, Aggi Panigoro; Rizkiani, Meti Agni; Amni , Muhammad; Libertia, Yosi; Sugiarta, Nugraha; Ilham, Yanuar; Lestari, Anggita (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This community service focuses on the revitalization of pencak silat through the Serepan Patalekan Usik Sanyiru festival, by utilizing digital technology based on cultural visualization as an effort to create the first Penca Village tourism destination in West Java. The background of this service arises from concerns about the loss of the pencak silat tradition as an intangible cultural heritage recognized by UNESCO. The main purpose of this activity is to revive the public's interest in pencak silat, as well as to increase people's understanding and skills in preserving this martial art. The methods used in this community service include socialization and training for the community about the Usik Sanyiru Matching pencak silat technique, as well as the application of digital technology to support promotion and documentation. This activity also involved students and lecturers from the Indonesian University of Informatics and Business in the revitalization process held in Jayagiri Village. The results of the service show an increase in community participation in pencak silat activities, as well as the formation of an active pencak silat community. In addition, the use of social media and digital technology in festival promotion has also succeeded in increasing awareness of the existence of pencak silat art among the younger generation. By directly involving the community and utilizing technology, this activity not only has a positive impact on the preservation of local culture, but also contributes to the development of the tourism industry in the area